2013
DOI: 10.1098/rsob.130035
|View full text |Cite
|
Sign up to set email alerts
|

A new role for muscle segment homeobox genes in mammalian embryonic diapause

Abstract: Mammalian embryonic diapause is a phenomenon defined by the temporary arrest in blastocyst growth and metabolic activity within the uterus which synchronously becomes quiescent to blastocyst activation and implantation. This reproductive strategy temporally uncouples conception from parturition until environmental or maternal conditions are favourable for the survival of the mother and newborn. The underlying molecular mechanism by which the uterus and embryo temporarily achieve quiescence, maintain blastocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 37 publications
3
74
0
Order By: Relevance
“…In the mouse without diapause, expression is transient at early day 4. In contrast, during diapause, Msx1 is highly expressed, and in mice with conditional uterine inactivation of Msx1 and Msx2 there is reduced blastocyst recovery and survival (Cha et al, 2013). These mice also fail to achieve true delay, suggesting that the entry into diapause is under maternal control.…”
Section: Muscle Segment Homeobox Gene Msxmentioning
confidence: 85%
See 3 more Smart Citations
“…In the mouse without diapause, expression is transient at early day 4. In contrast, during diapause, Msx1 is highly expressed, and in mice with conditional uterine inactivation of Msx1 and Msx2 there is reduced blastocyst recovery and survival (Cha et al, 2013). These mice also fail to achieve true delay, suggesting that the entry into diapause is under maternal control.…”
Section: Muscle Segment Homeobox Gene Msxmentioning
confidence: 85%
“…These mice also fail to achieve true delay, suggesting that the entry into diapause is under maternal control. Oestrogen and progesterone do not directly induce Msx1 but in mice, the effects of Msx genes in diapause are mediated through Wnt5a, a known transcriptional target of uterine Msx (Cha et al, 2013, Nallasamy et al, 2012. Interestingly, Msx1 expression persists in Lif --/ -mice but LIF injection induces implantation and downregulation of Msx1 expression (Cha et al, 2013; also see below).…”
Section: Muscle Segment Homeobox Gene Msxmentioning
confidence: 99%
See 2 more Smart Citations
“…This concept is It was later shown that an ovarian surge of estradiol secretion during late morning of the fourth day following mating is essential to induction of implantation (McCormack and Greenwald, 1974). Much of what we know about rodent implantation can be attributed to use of an experimentally induced diapause model, the ovariectomized, progesterone-treated mouse or rat, in which implantation can be predictably induced by a single administration of estrogen (Cha et al, 2013).…”
Section: B C Amentioning
confidence: 99%